Physicians in the substance abuse treatment workforce: Understanding their employment within publicly funded treatment organizations - Knudsen, Hannah K. (2012)
The employment of physicians by substance abuse treatment organizations is understudied, despite physicians' importance in implementing pharmacotherapy and integrating treatment into the broader system of medical care. Drawing on data collected from 249 publicly funded treatment organizations, this study examined organizational and environmental factors associated with the employment of physicians in these settings. A negative binomial regression model indicated greater numbers of physicians were employed when organizations offered detoxification services, were embedded in health care settings, and were larger in size. Funding barriers, including the costs of physicians and inadequate reimbursement by funders, were negatively associated with physician employment. Programs unaware that they could use state contract funding to pay for medical staff employed fewer numbers of physicians than programs aware of this type of state policy. Attempts to increase physician employment in substance abuse treatment may require attention to both organizational and environmental factors rather than simply trying to attract individuals to the field. Increasing physician employment may be challenging in the current economic climate.